2014
DOI: 10.1159/000366262
|View full text |Cite
|
Sign up to set email alerts
|

Do Immunocompromised Children Benefit from Having Surgical Lung Biopsy Performed?

Abstract: Background: Surgical lung biopsy is considered a gold standard for the evaluation of pulmonary disease in immunocompromised children. However, in the literature, its accuracy and the rate of complications vary. Objective: We aimed to evaluate the yield of surgical lung biopsies in the management of persistent pulmonary findings in immunocompromised children. Methods: We performed a retrospective review of clinical records of immunocompromised children who underwent surgical lung biopsies, and evaluated the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…White et al [11] demonstrated that surgical lung biopsy yield was decreased among neutropenic patients who recently received pulmonary toxic chemotherapy and were on mechanical ventilation at the time of biopsy. Similarly, other groups have previously demonstrated that among immunocompromised children following stem cell transplant, surgical lung biopsy rarely redirected therapy and did not improve outcomes [12,13]. These data highlight the need for careful consideration of the risks and benefits of surgical lung biopsy among these acutely ill patients.…”
Section: Discussionmentioning
confidence: 76%
“…White et al [11] demonstrated that surgical lung biopsy yield was decreased among neutropenic patients who recently received pulmonary toxic chemotherapy and were on mechanical ventilation at the time of biopsy. Similarly, other groups have previously demonstrated that among immunocompromised children following stem cell transplant, surgical lung biopsy rarely redirected therapy and did not improve outcomes [12,13]. These data highlight the need for careful consideration of the risks and benefits of surgical lung biopsy among these acutely ill patients.…”
Section: Discussionmentioning
confidence: 76%
“…It is also used in therapy of metastases in sarcomatous lesions, such as osteosarcoma, soft tissue sarcoma and chondrosarcoma, as well as non-sarcomatous lesions such as colorectal cancer, hepatocellular carcinoma, breast cancer, renal cell carcinoma, squamous cell gynaecological cancer, adenoid cystic cancer, biliary cancer and germ cell tumor [4,5]. Lung biopsy is a valuable diagnostic method in diagnosis of nonmalignant diseases, including infectious [1,[6][7][8] and non-infectious [9][10][11][12] complications after stem cell transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical lung biopsy (SLB) is often considered in an attempt to secure a definitive diagnosis and guide therapeutic decisionmaking. SLB is uniquely valuable in that it provides tissue for histopathologic interrogation even though the reported diagnostic yield is variable, ranging from 37% to 97% [12,[15][16][17]. The impact of SLB on the management of HSCT recipients with pulmonary complications is not clear because subsequent changes in therapy are reported to occur in 40% to 90% of patients [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%